El Plan Miner como instrumento de reactivación de las cuencas mineras leonesas = The MINER plan as an instrument for the socioeconomic reactivation of the León mining basins - Rodríguez Lago, Julio (Polígonos. Revista de Geografía, 2013)
El presente artículo analiza las líneas maestras y la efectividad del reciente plan diseñado por el Ministerio de Industria y Energía para combatir los efectos negativos que la desaparición de la industria carbonífera origina en el entorno de las cuencas mineras españolas, actuando como marco geográfico de referencia para acometer esta acción analítica las comarcas mineras de León. This article analyses the main points and effectiveness of the recent plan designed by lhe lndustry and Energy Department so as to fight the negative eflects caused by the disappearance of the coal industry in Spanish coalfields. The mining regions of León are taken as the geographical frame of refcrence in order to undertake this analytic action.